Evaluation of the good agricultural practices of dairy farms in Serra Gaúcha-RS (Research, Society and Development, 2021)
The Good Agricultural Practices (GAP) in milk production constitute a set of activities developed within the rural property in order to ensure the health, welfare and safety of animals, humans and the environment. Thus, the work aimed to evaluate compliance with the GAP implemented in the execution of the qualification plan for milk suppliers established by the Normative Instruction (IN) No. 77/2018 of the Ministry of Agriculture, Livestock and Supply (MAPA) in 12 properties in Serra Gaúcha-RS of which the sixteen items of this legislation were analyzed. The items of major nonconformities are the integrated pest control (96%), personal hygiene and training of workers (92%), rational use and storage of chemicals, toxic agents and veterinary drugs (82%), and lack of information distribution of technical material such as manuals and booklets (67%) indicating a low level of adequacy to GAP in the dairy sector in what the legislation advocates in the visited properties, thus demonstrating the need to increase quality actions so that there are improvements in relation to the physical-chemical and microbiological integrity of raw refrigerated milk produced by these rural producers.